2014
DOI: 10.1038/nphys2978
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent amplification of magnetic fields in laboratory laser-produced shock waves

Abstract: X-ray 1-3 and radio 4-6 observations of the supernova remnant Cassiopeia A reveal the presence of magnetic fields about 100 times stronger than those in the surrounding interstellar medium. Field coincident with the outer shock probably arises through a nonlinear feedback process involving cosmic rays 2,7,8 . The origin of the large magnetic field in the interior of the remnant is less clear but it is presumably stretched and amplified by turbulent motions. Turbulence may be generated by hydrodynamic instabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
75
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 29 publications
1
75
0
Order By: Relevance
“…3B. Translated into wavenumber spectrum, this spectrum is MðkÞ ≈ k −17=9 (see Supporting Information), substantially shallower than the low-Rm Golitsyn spectrum k −11=3 (29), which we observe in the case of no jet collision, so both less turbulence and lower Rm (10). The emergence of progressively shallower magnetic spectra is a sign of nonlinear field amplification, which is a precursor to turbulent dynamo (31).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…3B. Translated into wavenumber spectrum, this spectrum is MðkÞ ≈ k −17=9 (see Supporting Information), substantially shallower than the low-Rm Golitsyn spectrum k −11=3 (29), which we observe in the case of no jet collision, so both less turbulence and lower Rm (10). The emergence of progressively shallower magnetic spectra is a sign of nonlinear field amplification, which is a precursor to turbulent dynamo (31).…”
mentioning
confidence: 85%
“…Details are given in ref. 10. The initial (t < 100 ns) high-frequency noise due to the laser-plasma interaction with the target has been filtered.…”
mentioning
confidence: 99%
“…Besides being of astrophysical (origin of observed fields) and fundamental (what happens?) physical interest, it is likely soon to be attacked not just theoretically, but also experimentally, with the advent of laboratory experiments aiming to reproduce the plasma dynamo process (Spence et al 2009;Meinecke et al 2014Meinecke et al , 2015Plihon et al 2015;Forest et al 2015). The first demonstration of this process in a 3D kinetic numerical simulation by Rincon et al (2016) has indeed confirmed the ubiquitous appearance of mirror and firehose fluctuations, although a detailed investigation of the full multiscale problem remains computationally too intensive to be affordable.…”
Section: Introductionmentioning
confidence: 99%
“…Much progress has been made in recent years on understanding the generation and transport of these fields in high-energy-density plasmas [12], motivated by problems in laboratory astrophysics [13], magnetic reconnection [14][15][16][17][18], hydrodynamic-instability growth [19], shock-wave dynamics [20][21][22], and inertial confinement fusion [23]. In these conditions, much attention has been given to understanding the Biermann battery mechanism [24] and the magnetic fields that can be generated at the surface of a laser-irradiated solid target [25].…”
mentioning
confidence: 99%